Prognostic factors in the primary care of patients with Merkel cell carcinoma: A monocentric cohort study of 108 patients from a tertiary referral centre - Jan‐Malte Placke; Maximilian Zahn; Hannah Zillikens; Frederik Krefting; Georg C. Lodde; Lisa Zimmer; Elisabeth Livingstone; Eva Hadaschik; Antje Sucker; Alexander Roesch; Alpaslan Tasdogan; Nalini K. Srinivas; et al. (Wiley, 2023)
Abstract Background Merkel cell carcinoma (MCC) is one of the deadliest skin cancers. Despite existing national guidelines, treatment of MCC patients is not as well standardized as for more common skin cancers. Objectives The study objective was to investigate factors predisposing to favourable/unfavourable patient outcomes and to which extent guideline‐based care affects patient survival. Methods This noninterventional study investigated a monocentre real‐world patient cohort with a histologically confirmed diagnosis of MCC who presented at the skin cancer centre, University Hospital Essen. Patient and tumour characteristics (age, sex, primary localization, Merkel cell polyomavirus [MCPyV], tumour stage at initial diagnosis and primary treatment measures [surgery, radiation]) were correlated with the patient outcome in terms of recurrence‐free survival (RFS) and overall survival (OS). Results A total of 108 patients were identified. The median age of the patients was 69.9 years (range 39-88), with patients aged <70 years showing a trend towards a longer RFS (p = 0.192). Regarding sex, 69 (63.9%) of the patients were male, with females showing a trend towards a longer RFS (0.189). MCPyV+ primary tumours are less frequently located in the head/neck region (p = 0.003). Patients with primary tumours in the head/neck region had a significantly worse OS than patients with primary tumours at the trunk/extremities (p = 0.007). Patients with positive sentinel lymph nodes (SLNs) showed a tendency towards shorter RFS (p = 0.126) and OS (p = 0.089). Patients with American Joint Committee on Cancer stages I, IIA and IIB had a slightly better RFS (p = 0.803) and OS (p = 0.820) compared to patients with stages IIIA and IIIB. Moreover, the administration of adjuvant radiotherapy resulted in a slightly better RFS (p = 0.299) and OS (p = 0.276) in patients with tumour stages I, IIA and IIB. Conclusions In the present study, the outcome of MCC patients depended on primary tumour localization, SLN status, sex and age. The tumour stage and the adjuvant radiation had only limited effects on patient outcomes.